EXAMINING HIGHER ORDER THINKING IN INDONESIAN LOWER SECONDARY MATHEMATICS CLASSROOMS - Citra Putriarum Tanudjaya; Michiel Doorman (Journal on Mathematics Education, 2020)
Indonesian students’ poor performance in the mathematics test of PISA 2015 prompted the decision by the Ministry of Education of Indonesia to pay more attention to the integration of higher-order thinking (HOT) in the curricula starting in 2018. This new regulation emphasizes the need to have a shared understanding of HOT in mathematics on many levels, such as curriculum, pedagogy, and assessment, and among students, teachers and policy makers. This study aims to examine HOT in Indonesian lower secondary mathematics classrooms by assessing students’ ability to demonstrate HOT skills through an open-ended mathematics problem, and by exploring teachers’ views of HOT skills through semi-structured interviews. It involved 372 ninth-grade students and six mathematics teachers from six lower secondary schools in Jakarta and Palembang. The findings show that most students could construct the mathematical model but experienced difficulty in transferring knowledge into new contexts, in applying creative thinking, and with information literacy skills. Besides, some of the teachers were familiar with the concept of HOT, but some viewed HOT as skills for talented students, or HOT problems having a high level of difficulty and long storylines. The knowledge of existing teaching strategies, familiarity with HOT problems, and colleague-support are needed to improve the development of HOT skills in the mathematics classroom.